A New Approach to Determine Eps Parameter of DBSCAN Algorithm - Ozkok, Fatma Ozge; Celik, Mete (International Journal of Intelligent Systems and Applications in Engineering, 2017)
In recent years, data analysis has become important with increasing data volume. Clustering, which groups objects according to their similarity, has an important role in data analysis. DBSCAN is one of the most effective and popular density-based clustering algorithm and has been successfully implemented in many areas. However, it is a challenging task to determine the input parameter values of DBSCAN algorithm, which are neighborhood radius, Eps, and minimum number of points, MinPts. The values of these parameters significantly affect clustering performance of the algorithm. In this study, we propose AE-DBSCAN algorithm, which includes a new method to determine the value of neighborhood radius Eps automatically. The experimental evaluations showed that the proposed method outperformed the analytical DBSCAN.